Photoenzymatic enantioselective synthesis of fluorinated amides with remote stereocenter - Chaoqun Huang; Xuerui Jin; Zhenyu Liu; Can Cui; Yang Zhang; Binju Wang; Chun Zhang; Jianqiang Feng; Dawen Niu; Yunzi Luo (Nature Communications)
Abstract Fluorinated compounds are scarce in nature, albeit they are in high demand in pharmaceuticals, agrochemicals, and materials. Fluorinated amides serve as prevalent structural motifs in pharmaceuticals and bioactive molecules. However, enantioselective synthesis of fluorinated amides remains challenging. Herein, we develop a visible-light-driven ene-reductase system that effectively generates carbon-centered radicals from fluorine-containing brominated amides. The system further enables their enantioselective hydroalkylation with alkenes, achieving high stereocontrol. Diversified α-fluorinated amides with high yield (up to 91%) and distal chirality (γ-to F, up to 97% enantiomeric excess) are produced by optimizing the reaction system and performing enzyme engineering. This work advances photoenzymatic strategies for the integration of fluorinated chemical inputs and creates an opportunity for the asymmetric synthesis of valuable fluorinated compounds.